Enhancing Product Quality and Process Capability in the Indonesian Furniture Industry through Six Sigma DMAI Implementation: A Case Study on Laminating Defects - Retnowati, Dini; Priyanto, Rido Agus; Widya Ardhyani, Ika; Anshori, Moch (IQTISHADequity jurnal MANAJEMEN, 2024)
Product quality is critical in today's competitive business environment, as it determines customer satisfaction, operational efficiency, and market competitiveness. Variability in the production process is often the main cause of product defects, which lowers customer satisfaction and increases production costs. The Six Sigma method with the DMAI (Define, Measure, Analyze, Improve) approach can reduce variability and improve process capability. This study focuses on implementing Six Sigma in the Indonesian furniture industry, which saw a 28.93% increase in export value in 2021 but still needs to improve with product quality consistency. One furniture manufacturer experienced a laminating defect rate of 3%, exceeding the company's standard of 1%. Through the DMAI phases, this research identifies the leading causes of defects and develops improvement recommendations. Analysis using control charts, DPMO, Pareto diagrams, FMEA, and RCA revealed that most defects are caused by human factors, such as operators not performing machine checks and cleanings and using wooden pallets that do not meet standards. Improvement recommendations include creating standard checklists, conducting regular training, and implementing monitoring systems for machine checks, pallet cleaning, and setting pallet standard specifications. Implementing Six Sigma is expected to improve process capability, reduce defects, and enhance the company's competitiveness in the global market.